A Comparative Study of Sound Resonance Using Arduino-Based Ultrasonic Sensors and Visualization Analysis with Python - Iskandar, Feri; Pramudya, Yudhiakto (Universitas Sebelas Maret, 2024)
In the modern era, the study of sound resonance in physics laboratories has increasingly incorporated technological tools to improve the experimental process. While conventional approaches to resonance experiments remain common, they often face challenges related to equipment setup and limited real-time data analysis. This research compares conventional methods with Arduino-based techniques, combined with Python for data visualization and analysis, in sound resonance experiments. The integration of Arduino microcontrollers and ultrasonic sensors offers a more accessible and streamlined alternative to conventional resonance measurement techniques, facilitating improved data collection and interpretation. Data is gathered using PLX DAQ software connected to the Arduino system, with the results visualized and analyzed using Python tools. The experiments show that the average air column length when the water in the reservoir was lowered is 16.10 cm, with an error of 3.04%, and when the water was raised, the average length is 15.60 cm, with an error of 5.98%. A 512 Hz sound source was used to determine the fundamental frequency, revealing slight variations due to changes in the measurement distance. Specifically, the fundamental frequency was recorded as (528 ± 5) Hz when the water level was lowered and (545 ± 8) Hz when it was raised. This study highlights the positive role of technology in enhancing physics education and research, particularly in sound resonance studies.